2007
DOI: 10.1086/510895
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Thermal Coronae of Galaxies in Hot Clusters: Ubiquity of Embedded Mini–Cooling Cores

Abstract: We present a systematic investigation of X-ray thermal coronae in 157 early-type galaxies and 22 late-type galaxies from a survey of 25 hot (kT > 3 keV), nearby (z < 0.05) clusters, based on Chandra archival data. Cool galactic coronae (kT = 0.5 -1.1 keV generally) have been found to be very common, > 60% in NIR selected galaxies that are more luminous than 2 L * , and > 40% in L * < L Ks < 2 L * galaxies. These embedded coronae in hot clusters are generally smaller (1.5-4 kpc radii), less luminous ( < ∼ 10 41… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
269
3
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(304 citation statements)
references
References 95 publications
28
269
3
2
Order By: Relevance
“…This apparent paucity of objects is expected assuming a virial origin for the heating of the gas. By comparing our sample to the simplest theoretical prediction for the virial gas temperature, such that b m s = m kT p spec 2 gas , where m p is the mass of a proton, mm p is the mean particle mass with m = 0.62, and k is the Boltzmann constant (e.g., Loewenstein & White 1999;Loewenstein 2000;Sun et al 2007;Jeltema et al 2008;Pellegrini 2011), we show that within the measurement uncertainties, no galaxies considered here have b > 1 spec , suggesting that a virial model provides a lower boundary to the observed gas temperature in early-type galaxies (e.g., Cox et al 2006). Hence, we find good evidence that in all systems, the minimum gas temperature, T gas,min , goes as s e 2 .…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…This apparent paucity of objects is expected assuming a virial origin for the heating of the gas. By comparing our sample to the simplest theoretical prediction for the virial gas temperature, such that b m s = m kT p spec 2 gas , where m p is the mass of a proton, mm p is the mean particle mass with m = 0.62, and k is the Boltzmann constant (e.g., Loewenstein & White 1999;Loewenstein 2000;Sun et al 2007;Jeltema et al 2008;Pellegrini 2011), we show that within the measurement uncertainties, no galaxies considered here have b > 1 spec , suggesting that a virial model provides a lower boundary to the observed gas temperature in early-type galaxies (e.g., Cox et al 2006). Hence, we find good evidence that in all systems, the minimum gas temperature, T gas,min , goes as s e 2 .…”
Section: 3mentioning
confidence: 99%
“…The L X,gas -T gas relation may further steepen in the poorest groups and individual galaxy halos as the hot gas surrounding the galaxies is no longer virialized and/or is dominated by other effects. Previous studies have sought to link these differing structural scales to provide a coherent picture of the X-ray properties of the most massive systems in the universe (e.g., O'Sullivan et al 2003;Khosroshahi et al 2007;Sun et al 2007Sun et al , 2009Diehl & Statler 2008;Mulchaey & Jeltema 2010;Vajgel et al 2014). However, observational evidence for the hot-gas origin is still in question.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies, mainly using ROSAT data, found no correlation e.g., O'Sullivan et al 2001. More recent Chandra studies of groups and clusters (e.g, Jeltema et al 2008;Sun et al (2007)) seem to confirm a general anti-correlation of local density and X-ray luminosity. Observations of several galaxies in nearby clusters show evidence for ram pressure stripping; examples include M86 (Randall et al 2008) and NGC 4552 (Machacek et al 2006).…”
Section: Environmental Effects On X-ray Emissionmentioning
confidence: 95%
“…Observations of several galaxies in nearby clusters show evidence for ram pressure stripping; examples include M86 (Randall et al 2008) and NGC 4552 (Machacek et al 2006). However, despite the efficiency of stripping, most bright early-type galaxies in clusters do retain small coronae (Sun et al (2007)). …”
Section: Environmental Effects On X-ray Emissionmentioning
confidence: 99%
“…However, recent studies with Chandra, which is better able to resolve galaxy emission, show that LX /LB is suppressed by a factor ∼3-4 in non-central galaxies within both clusters (Sun et al (2007)) and groups (Jeltema et al (2008)). This presumably results from stripping of hot gas within dense environments.…”
Section: Sources Of Scatter In L X -L Optmentioning
confidence: 99%